Italian Communication on the Revolt in the Low Countries (1566-1648) - Lamal, Nina, author.
1 online resource
Keywords: This groundbreaking book is the first comprehensive study of Italian communication on the Revolt in the Low Countries. Nina Lamal provides a compelling account of the deep Italian involvement in this long conflict, also known as the Eighty Years’ War. Drawing upon a wide range of sources in manuscript and print, including newsletters, printed pamphlets, political treatises and historical narratives, Lamal investigates how news on the conflict was brought to the Italian peninsula, how it influenced political debates as well as historical discourses. She unravels why it had such an impact in this complex political environment. In doing so, she also casts new light on the meaning of the Revolt itself.